Penerapan Metode 360 Derajat Dan Analytic Hierarchy Process(AHP) Sebagai Penilaian Kinerja Karyawan Pada CV Mainan Kayu - Dwi Andiani Astuti; Arif Rahman (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
CV. Wooden Toys is a manufacturing company that is engaged in making educational wooden toyswhich are made from wood. The number of similar businesses that are currently developing is thebiggest challenge for CV. Wooden Toys to compete. Based on the results of interviews that havebeen conducted, this company has several problems, including a decrease in the number of salesfor the January-September 2019 period, late delivery, product damage that occurs due to thedelivery process, and an objective assessment of employee performance. Judging from theproblems that occur, researchers will conduct research on the performance appraisal of employeesof CV. Wooden Toys in the sales and marketing section. E. The purpose of this research is todetermine the results of the employee performance appraisal at CV Toys Kayu using 360 degreesand AHP methods. The research method used is the 360 degree method and Analytic HierarchyProcess (AHP). The 360 degree method provides assessments with various angles includingassessments given by superiors, coworkers and yourself, while the Analytic Hierarchy Process(AHP) method is used to determine the weighting of variables and subvariables that affect the employee performance appraisal which will be used as material in distributing questionnaires.From the results of the integration research of AHP and the 360 Degree Method that has beencarried out, the results of the performance appraisal in the online sales center section are equal to5.65, sales representives equal to 5.98, wholesale sales equal to 5.99, adm supervisor equal to6.69, and administration equal to 6.55. The priority variable that affects the employee performanceappraisal of CV Toys Kayu is a general trait where the general characteristic has a fairly highweight value, namely 0.390. While the priority subvariable that most influences the performanceappraisal of employees of CV Toys Kayun is innovative where innovative has a weight value equalto 0.390